Nitrogen kinetics in growing sheep consuming Leucaena leucocephala, Gliricidia sepium or Calliandra calothyrsus as a sole diet - Widiawati, Yeni; Winugroho, M; Teleni, E (Indonesian Animal Sciences Society, 2012)
The utilization of protein feed by animals are influenced by the process of its degradation in the rumen and its digestion in the intestine. The extent of its degradation and digestion are influenced by the form of protein and the present of secondary compound in the plant. The aim of the study was to determine the amont of protein in the three leguminouse shrubs utilized by the animals. The study on the utilization of protein from leguminouse shrub was undertaken by investigate the nitrogen kinetic in 24 head of growing sheep (BW 23kg) consuming Leucaena leucocephala, Gliricidia sepium, Calliandra callothyrsus leaves and Rhodes grass hay. The diets were fed every two hours starting at 07:00 am. The animals were divided into four groups of dietary treatment namely LL, GS, CC and CG groups which were fed by Leucaena, Gliricidia, Calliandra dan Rhodes grass leaves, respectively. The Rhode grass, as control diet, was mixed with 1.4% of urea to increase the nitrogen offered to the animals up to 150 g/day. Thus all the four diets were offered the same amount of nitrogen/day. Measurements were undertaken on feed utilization and nitrogen kinetics in experimental animals. The amount of nitrogen consumed then undegraded in the rumen as well as undigested in the intestine was significant higher in CC group (P < 0.01) then those in LL, GS and CG groups. The value was 67% for CC group then followed by 35% for LL group and 33% for GS group. The amount of nitrogen degraded in the rumen thus lost in urine was significantly higher in animals fed GS and LL leaves compared to those in animals fed CC diet (P < 0.01). The values were 46% for GS and LL group and only 16% for CC group. The amount of nitrogen retained by the animals was similar among the three groups being 17-21% (P > 0.05). The Plasma urea concentration, urea entry rate and urea in urine animals were similar in LL and GS groups but higher than those in CC group. The values were 0.86; 0.8; 0.46 mg/ml (P < 0.01) and 79; 78; 50 g/d (P < 0.01) and 26.7; 24.5; 7.3 g/d (P < 0.01) for LL, GS and CC groups, respectively. The conclusion is most of nitrogen from Calliandra was un-degraded and un-digested in the rumen and intestine thus excreted through feces, while most of the protein in Leucaena and Gliricidia was degraded in the rumen thus excreted through urine. Key Words: Leucaena, Gliricidia, Calliandra, Nitrogen-Kinetics, Urea Entry Rate